Revision anterior cruciate ligament reconstruction using a 2-stage technique with bone grafting of the tibial tunnel. - Thomas, N; Kankate, R; Wandless, F; Pandit, H (2005)
BACKGROUND: Revision anterior cruciate ligament surgery is often considered a salvage procedure with limited goals. However, this limitation need not be the case. Similar to primary reconstruction, the goal should be to choose an appropriate graft and place it in an anatomical position in a good quality bone. The issue of good quality bone seems to have been ignored. HYPOTHESIS: A 2-stage anterior cruciate ligament revision reconstruction with bone grafting of the tibial tunnel and the use of a different femoral tunnel will produce measured knee laxity and International Knee Documentation Committee scores similar to a primary anterior cruciate ligament reconstruction. STUDY DESIGN: Case control study; Level of evidence, 3. METHODS: This prospective study involved 49 consecutive 2-stage anterior cruciate ligament revisions (group R) performed by a single surgeon from 1993 to 2000. Two-stage revision surgery was performed if the tibial tunnel from a previous reconstruction surgery would overlap (either partially or fully) the correctly placed revision tunnel. The first stage consisted of removal of the old graft and interfering metalwork, together with bone grafting of the tibial tunnel. After ensuring adequate bone graft incorporation using computed tomography scan, the second stage revision was undertaken. This stage comprised harvesting the autograft, its anatomical placement, and its adequate fixation. The results were compared with the results of a matched group of patients with primary anterior cruciate ligament reconstruction (group P). RESULTS: In group R, as meniscal and chondral lesions were more common, the International Knee Documentation Committee scores were lower than those of group P (61.2 for group R and 72.8 for group P; P = .006). Objective laxity measurement was similar in both groups (1.36 mm for group R and 1.2 mm for group P; P = .25). CONCLUSION: This study establishes that the laxity measurements achieved with a 2-stage revision anterior cruciate ligament reconstruction can be similar to those achieved after primary anterior cruciate ligament reconstruction, although the International Knee Documentation Committee rating is lower.